2006
DOI: 10.1002/jcp.20674
|View full text |Cite
|
Sign up to set email alerts
|

Dopamine regulates cell cycle regulatory proteins via cAMP, Ca2+/PKC, MAPKs, and NF‐κB in mouse embryonic stem cells

Abstract: This study examined the effect of dopamine on DNA synthesis and its related signal cascades in mouse embryonic stem (ES) cells. Dopamine inhibited DNA synthesis in both a dose- and time-dependent manner. Dopamine, SKF 38393 (D1 receptor agonist), and quinpirole (D2 receptor agonist) decreased the level of [(3)H]-thymidine incorporation. The level of cyclic adenosine 3, 5-monophosphate (cAMP) was increased by SKF 38393 but not by quinpirole. The protein kinase C (PKC) protein was translocated from the cytosolic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
17
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 41 publications
0
17
0
Order By: Relevance
“…In certain conditions D2 stimulation did not activate p38 [41]. Nevertheless, it was recently shown that dopamine itself, and either D1 agonist or D2 agonist, all induce various MAPKs activation [50]. In spite of this research, coincidence detection between NMDA and dopamine signaling has not been determined in any of the MAPK family members.…”
Section: Discussionmentioning
confidence: 94%
“…In certain conditions D2 stimulation did not activate p38 [41]. Nevertheless, it was recently shown that dopamine itself, and either D1 agonist or D2 agonist, all induce various MAPKs activation [50]. In spite of this research, coincidence detection between NMDA and dopamine signaling has not been determined in any of the MAPK family members.…”
Section: Discussionmentioning
confidence: 94%
“…Likewise, several reports indicate that nuclear factor (NF)-KB1, a family of dimeric transcription factors that regulates cell division, apoptosis, and inflammation, could be activated through EGF or EGFR system [13][14][15]. In addition, the Ca 2þ /PKC, NFKB1 signal pathway was found to mediate DNA synthesis in mouse embryonic stem cells [16]. Furthermore, Ge et al [17] demonstrated that PKC-linked NFKB1 activation modulated ginsenoside-stimulated proliferation of chicken PGCs.…”
Section: Introductionmentioning
confidence: 96%
“…Previous reports have shown that D1, D4, and D5 message is expressed in human neural progenitors, while human EBs, but not hESCs, have been shown to express D1 mRNA [46,47]. In addition, mouse ESCs have been shown to express D1 and D2 receptors [48]. In rat embryos, D1 and D2 receptors are found in the striatum at least by E14 [49].…”
mentioning
confidence: 94%